Are Cognitive Biases the Hidden Force Shaping Malaysia’s Healthcare System? - Maspul, Kurniawan Arif; Ardhin, Muhammad; Hendra Prasetyo (ROE: Research of Economics and Business, 2025)
Cognitive biases silently shape Malaysia’s healthcare system, influencing clinical decisions, patient safety, and the nation’s thriving medical tourism industry. While Malaysia excels in affordability and innovation, biases such as confirmation, overconfidence, and anchoring distort diagnoses, amplifying malpractice risks and ethical dilemmas. A 2023 case in Kuala Lumpur exposed life-threatening failures in cosmetic surgery tourism, underscoring systemic blind spots (The Strait Times, 2023). This study integrates macroeconomic analysis, AI-driven diagnostics, and cognitive theory to unravel the hidden forces jeopardizing medical integrity. Findings reveal a paradox: cutting-edge advancements coexist with workforce shortages, defensive medicine, and bias-driven errors. To safeguard Malaysia’s global reputation, this research advocates for AI-enhanced decision-making, cognitive bias training, and strategic workforce expansion. Beyond critique, this work presents a visionary roadmap—one that embeds cognitive resilience into healthcare strategy, ensuring that economic ambition never eclipses ethical imperatives. Malaysia stands at a crossroads: its future as a medical powerhouse depends on its ability to balance innovation, trust, and the sanctity of patient well-being